PENGARUH MOTIVASI BELAJAR DAN PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR IPS SISWA KELAS IV DI SDN MAYANGAN 6 KOTA PROBOLINGGO - Susi Andriani (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2016)
This research aims to know the influence of learning motivation and the use of instructional media on learning achievement of sixth graders at SDN Mayangan 6 Probolinggo. Thirty three (33) students were invoked as the participants. As the result, it shows that there is a significant influence of learning motivation on learning achievement, the use instructional media on learning achievement, and learning motivation and the use of instructional media simultaneously on learning achievement of sixth graders at SDN Mayangan 6 Probolinggo.